Bobus1711
Rozwiązane

Proszę o pomoc
Uprość wyrażenia:

(3x - y + 2) + (-5x +4y -6) =

(2ab - 4b + 3a) - ( 4a - 2b + 5ab) =

3 (2x + 6) + 5 (x - 7) =

x (3x - 4) - 2 ( x + 1) =

(a - 12b) : 5 - ( 4a + b) : 2 =

2x + 14y2- 5x +15y5 =

9a - 6b-3+ 10a - 5b2=

(x + 5) (x - 2) =

(4a + 4b) (2a - 2b) =

- (3x - 3) (x + 2) =



Odpowiedź :

Odpowiedź:

a) 3x - y + 2 - 5x + 4y - 6 = -2x + 3y - 4

b) 2ab - 4b + 3a - 4a + 2b - 5ab = -a - 3ab - 2b

c) 6x + 18 + 5x - 35 = 11x - 17

d) 3x² - 4x -2x - 2 = 3x² - 6x - 2

e) [tex]\frac{a-12b}{5}[/tex] - [tex]\frac{4a+b}{2}[/tex] = [tex]\frac{2a - 24b}{10}[/tex] - [tex]\frac{20a+5b}{10}[/tex] = [tex]\frac{2a-24b-20a-5b}{10}[/tex] = [tex]\frac{-18a-29b}{10}[/tex]

f) 2x + 14y² - 5x + 15[tex]y^{5}[/tex] = 15[tex]y^{5}[/tex] + 14y² - 3x

g) 9a - 6b - 3 + 10a - 5b² = 19a - 6b - 5b² - 3

h) x² - 2x + 5x - 10 = x² + 3x - 10

i) 8a² - 8ab + 8ab - 8b² = 8a² - 8b² = 8(a² - b²)

j) - (3x² + 6x - 3x - 6) = -3x² - 6x + 3x + 6 = -3x² - 3x + 6 = -3(x² + x - 2)